Investigation of Toxoplasma gondii Infection in Aborted Fetuses of Sheep Using PCR: A Study in North Khorasan Province, Iran - Mitra Salehi; Hosein Nezami; Hamid Reza Niazkar (Veterinary Medicine International)
Toxoplasma gondii is a zoonotic obligate intracellular protozoan parasite that infects warm-blooded animals as well as humans worldwide. The purpose of this study was to delineate the prevalence of Toxoplasma infection in aborted fetuses of sheep in North Khorasan province, Iran. Three hundred and ninety-nine samples of the liver (133 samples), placenta (133 samples), and brain (133 samples) from 133 aborted fetuses of sheep were collected from 2015 to 2017. The ages of aborted fetuses were higher than 120 days’ gestational age in this study. According to the samples, sixteen out of 133 aborted fetuses of sheep were infected with T. gondii. Toxoplasma DNA was found in the placenta (68.75%) and liver (31.25%) samples of infected fetuses using the PCR method. The highest and lowest rates of Toxoplasma infection were observed during 2016 and 2017, respectively. Shirvan and Faruj provinces were recognized as the two most infected districts among others. There was a significant difference between the year and abortion rate in sheep due to infection by the Toxoplasma parasite (P<0.05). Furthermore, no significant difference between the prevalence of T. gondii infection and aborted fetuses was seen (P>0.05) in different areas. According to the present study, T. gondii infection can be one of the causes of fetus abortion of sheep in North Khorasan province, Iran.